(untitled) (Texas Journal of Medical Science, 2023)
The article provides information about the use of SGLT2 inhibitors in hypertensive crises, mechanisms of action as an antihypertensive drug and the normalization of endothelial function. Other generation of these drugs are also compared with empagliflazin. Studies have been conducted with placebo drugs, and information is given on the effect of drugs on reducing daily and night blood pressure.